THE ROLE OF LEARNING TECHNOLOGY "IN COLLABORATION" IN IMPROVING THE EFFICIENCY OF THE SCIENCE OF MEDICAL ELECTRONICS (Scientific journal of the Fergana State University, 2023)
In organizing and conducting a medical electronics lesson, the teacher can use various forms of teaching methods (lecture, oral presentation, problem solving, practical work, demonstration and other forms). It is also recommended to use various non-traditional teaching methods such as narration, question-and-answer, puzzles, debates, electronic manuals and multimedia. Based on the above, the teacher should be able to arouse students' creativity towards science with curiosity. The teacher should awaken in the student the aspiration that "I need medical electronics, I need to know it and be able to use it in my professional activity." To awaken this desire, the use of pedagogical technologies during the lesson gives an effective result.